Local rooting and creativity within the fashion industry in Beirut. Issue 2 (1st July 2019) - Ben Hassen, Tarek; Tremblay, Diane-Gabrielle
Abstract : Purpose: The purpose of this paper is to analyze the factors that make Beirut a fashion hub by studying the characteristics of creativity and the role of the different stakeholders in setting an environment that encourages creativity in Beirut. Design/methodology/approach: The methodology of this research is based on a literature review and information collected through semi-structured interviews with the different stakeholders of the sector. Findings: The research reveals three results. First, this dynamic fashion design in Beirut is explained by the international success of some Lebanese fashion designers. Second, as there is an absence of any form of governmental intervention, the development of the sector is totally based on private business initiatives. Third, the research demonstrates the importance of the local culture, knowledge exchanges and lifestyle in shaping creativity and designers' careers in Beirut. Originality/value: These findings contribute to the clarification and critical analysis of the current state of fashion design in Beirut, which would have several policy implications.